(untitled) (PANGEEA, 2025)
In recent years, Romania’s higher education landscape and labor market have undergone significant changes due to demographic factors, modernization, economic progress, and globalization. One notable transformation is the internationalization of higher education, which requires universities to align their curricula with labor market demands. Additionally, Romania has experienced growth in the service industry and increased involvement from multinational companies. However, little is known about the employment experiences of young people in the early years following graduation. This is particularly concerning given the significant rise in the number of university graduates occupying positions that do not match their educational qualifications or skill levels and those working in non-graduate professions. This study addressed this gap by using ethnographic case study data to analyze the experiences of young university graduates working as customer support representatives (CSRs). Informed by the social constructivism paradigm, data were collected through participatory observation, semi-structured interviews, and field notes and analyzed using a reflexive thematic analysis strategy. The results challenge employers’ claims of a lack of skills among young university graduates, emphasizing the need for a broader range of skills in the recruitment process and workplace. This study highlights the growing patterns of precarity affecting underemployed young Romanian graduates. The findings suggest that digital technologies used by outsourced companies deskill and diminish the dignity of CSR work, while work productivity strategies, measurement, and corporate working conditions create uncertainty in CSRs’ career prospects. Furthermore, it underscores that non-collaboration remains a significant issue in Romanian work culture, complicating the education-job mismatch. By shedding light on the university-to-work phenomenon and the value of higher education in the Romanian labor market, this study contributes to the sociology of work and employment by revealing that post-university trajectories are considerably diverse and necessitate further qualitative investigation beyond the educational outcomes typically discussed in the context of graduate employability.